2021
DOI: 10.3390/polym13244291
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Curcumin Nanoparticles Incorporated into Collagen-Alginate Scaffold on Wound Healing of Skin Tissue in Trauma Patients

Abstract: Wound healing is a biological process that is mainly crucial for the rehabilitation of injured tissue. The incorporation of curcumin (Cur) into a hydrogel system is used to treat skin wounds in different diseases due to its hydrophobic character. In this study, sodium alginate and collagen, which possess hydrophilic, low toxic, and biocompatible properties, were utilized. Collagen/alginate scaffolds were synthesized, and nanocurcumin was incorporated inside them; their interaction was evaluated by FTIR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…To reveal the best model for the curcumin release process from the PHEMA/G/A/TiO 2 hybrid scaffolds, the sum of the squared residuals (SSRs) and Akaike Information Criterion (AIC) was calculated and analyzed using four release kinetic models ( Table 2 ). The model with the smallest AIC value best describes the curcumin release phenomenon from the hybrid scaffolds [ 69 , 70 , 71 , 72 , 73 ]. Obtained AIC values indicated that Peppas–Sahlin and Peppas–Sahlin when m = 0.5 models best describe the curcumin release mechanism from obtained hybrid scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…To reveal the best model for the curcumin release process from the PHEMA/G/A/TiO 2 hybrid scaffolds, the sum of the squared residuals (SSRs) and Akaike Information Criterion (AIC) was calculated and analyzed using four release kinetic models ( Table 2 ). The model with the smallest AIC value best describes the curcumin release phenomenon from the hybrid scaffolds [ 69 , 70 , 71 , 72 , 73 ]. Obtained AIC values indicated that Peppas–Sahlin and Peppas–Sahlin when m = 0.5 models best describe the curcumin release mechanism from obtained hybrid scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that collagen plays a key role in wound healing, which promotes the healing activity (Mobaraki et al, 2021 ). In our study, gel with AgNPs having the concentrations of 0.5 and 1 mg g −1 was found to be effective for incision wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a number of NPs have been used in wound healing, such as polylactic-co-glycolic acid (PLGA)-curcumin NPs (Mobaraki et al, 2021 ), mucoadhesive NPs with enoxaparin (Yan et al, 2020 ), calcium-based NPs (Subramaniam et al, 2021 ), magnetic NPs (Noh et al, 2019 ), titanium dioxide NPs (Nikpasand and Parvizi, 2019 ), and copper NPs (Alizadeh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, hydrophobicity, low stability properties in physiological fluids as well as side effects including diarrhea, nausea, and reduction in cell proliferation, increased apoptosis, focal necrosis in the liver, as well as decreased body weight in a high dose of curcumin, can be major complications to achieve an efficient drug formulation (19,20). In addition to secondary metabolites of medicinal plants (21)(22)(23), natural polymers such as chitosan, cellulose, and collagen can increase the bioavailability and biodegradability of curcumin in micro and nanoformulations (24)(25)(26). Additionally, these polymers or their derivatives can contribute positively to the wound healing phase involving hemostasis, inflammation (inflammatory response, immune recruitment, and pathogen removal), proliferation, and maturation (Figure 2) (27,28).…”
Section: Introductionmentioning
confidence: 99%